2015
DOI: 10.1007/s00441-015-2233-5
|View full text |Cite
|
Sign up to set email alerts
|

Collagens and proteoglycans of the cornea: importance in transparency and visual disorders

Abstract: The cornea represents the external part of the eye and consists of an epithelium, a stroma and an endothelium. Due to its curvature and transparency this structure makes up approximately 70% of the total refractive power of the eye. This function is partly made possible by the particular organization of the collagen extracellular matrix contained in the corneal stroma that allows a constant refractive power. The maintenance of such an organization involves other molecules such as type V collagen, FACITs (fibri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 122 publications
4
59
0
4
Order By: Relevance
“…38 In addition to collagens, other ECM molecules, including proteoglycans, have a role in fibrillogenesis and matrix assembly in human corneas. 39 Recently, it was shown that one of the major corneal proteoglycans, LUM -encoding lumican, was downregulated in cell cultures derived from KTCN corneas and in the corneas. 34,40 In this study, the expression of LUM, was also diminished, which could destabilize normal corneal fibril organization.…”
Section: Discussionmentioning
confidence: 99%
“…38 In addition to collagens, other ECM molecules, including proteoglycans, have a role in fibrillogenesis and matrix assembly in human corneas. 39 Recently, it was shown that one of the major corneal proteoglycans, LUM -encoding lumican, was downregulated in cell cultures derived from KTCN corneas and in the corneas. 34,40 In this study, the expression of LUM, was also diminished, which could destabilize normal corneal fibril organization.…”
Section: Discussionmentioning
confidence: 99%
“…The beaded intermediate filaments (CP49 and filensin) have the outer diameter about 10–18 nm [Quinlan et al,1999], with some smaller nanoparticles organized around the filaments, being very important intermediate filaments in the eye lens fiber cells, determining their transparency [Tagliavini et al, 1986; Bloemendal, 1991; Marcantonio, Duncan, 1991; Rafferty et al, 1997; Matsushima et al, 1997; Clark et al, 1999; Alizadeh et al, 2002, 2003, 2004; Oka et al, 2008; Song et al, 2009]. Similarly, the transparency of the corneal cells also depends on the specialized collagen filaments [Jester, 2008; Massoudi et al, 2015]. …”
Section: Discussionmentioning
confidence: 99%
“…22,23 Collagenase has thus been implicated in corneal destruction after alkali-induced burn or other injury. [24][25][26] The expression of collagenase (MMP-1) has been found to be increased in association with destructive corneal disease.…”
Section: Discussionmentioning
confidence: 99%